The effect of sealant on prevention of enamel demineralization in patients with fixed orthodontic appliances: A systematic review - Gizani, Sotiria (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: One of the common problems of patients undergoing orthodontic treatment with fixed appliances is the evelopment of enamel demineralization. The objective of this review is to evaluate the effectiveness of sealants in preventing the occurrence of enamel demineralization in patients with fixed orthodontic appliances during treatment. Methods: A complex search was performed in Medline (1969 to May 2013), and by hand in individual articles, in order to identify any relevant study based upon various combinations of key words. The included studies are Randomized Controlled Trials (RCTs), or otherwise prospective clinical trials, with patients (teeth) of any age undergoing fixed orthodontic treatmentand with a control group or at least two intervention groups. In the absence of the above, any prospective cohort with more thanten patients was evaluated. To assess the internal validity of the eligible studies, the Cochrane Risk of Bias Tool for Randomized Clinical Trials was applied. Results: The searches originally identified 237 titles and abstracts, 6 fulfilled the inclusion criteria of the review. From these studies, 4 were randomized clinical trials and 2 prospective clinical trials. The results were contradictory, with half of the studies showing significant reductions in the incidence of enamel decalcification for the sealed teeth compared with the control group while the remaining half did not show any important differences. Discussion: Based on the findings from the present systematic review, it was impossible to make any reliable recommendations onthe usage of sealants during orthodontic treatment for the prevention of WSL development. Nevertheless, their use in general seems to be beneficial for caries prevention, depending on the type of material, the method of its application and the caries riskstatus of the patient.